PERENCANAAN PROSES CAD PRODUK BERKEPALA BAUT UNTUK APLIKASI CAM DENGAN MENERAPKAN METODE TO CORNER - Henri Viki Barapa; Rudy Poeng; Romels Cresano Apelles Lumintang (JURNAL POROS TEKNIK MESIN UNSRAT, 2012)
Computer is not just, a replacement for a typewriter, but also in the scope of graphic design, process data, animated recording is including in the art Computer Aided Design (CAD). Results of product design using CAD can be applied in Computer Aided Manufacturing (CAM) to simulate the machining process to work optimally, in using a computer to do programming, directing and controlling the production equipment based on the design of the product. This research is a study on how to simulate the process of CAD in shaping head bolt using AutoCAD software as a planning process. The purpose of this study is to planÂ  machining processes using shaping machine to get the CAD drawings as information for CAM applications. The results of this planning, the product is used as an object shaped head bolts (size 50x15 mm, and the size of the coordinates information obtained from motion trajectories Freis chisel upright in processing these products can be geomeotik code data for CAM applications by applying To Corner.